A Method for Designing Physical User Interfaces for Intelligent Production Environments. (16th August 2018) - Kirisci, Pierre Taner; Thoben, Klaus-Dieter
Abstract : Physical user interfaces with enhanced interaction capabilities are emerging along with intelligent production environments. In this manner, we pose the question if contemporary design methods and tools are sufficient for the design of this new breed of user interfaces, or if there is rather a need for more efficient design methods and tools. The paper is initiated with a discussion about the need for more sophisticated physical user interfaces with enhanced capabilities for interacting in intelligent production environments. Based on this idea, we derive several functional and nonfunctional requirements for a suitable design method, supporting the conceptualisation of physical user interfaces in the early phases of product development. Hence, we suggest a model-based design method, which incorporates a comprehensive context model and modelling tool, applicable to intelligent production environments. In order to demonstrate the feasibility of the design method, we further conduct a validation and evaluation of the functional modelling tool, based on an industrial use case, in cooperation with design experts. In the final section of the paper, we critically discuss the key characteristics of the design method and thus identify potential issues for future improvement.